Role of Azoles in Cancer Prevention and Treatment: Present and Future Perspectives - Ahmad, Khurshid; Khan, Mohd Kalim A.; Baig, Mohammad H.; Imran, Mohd; Gupta, Girish Kumar (Anti-Cancer Agents in Medicinal Chemistry, 2018)
Background: Cancer has gradually become one of the leading causes of death worldwide. The incidence of cancer among the population has increased alarmingly over the last two decades, primarily due to an increasing population of immune-compromised patients and the continuing rise in anti-cancer drug resistance. Azole found privileged structure in medicinal chemistry and pharmaceutical industry and also found to be showing antioxidant; antimicrobial, anthelmintic, anticancer, antiviral, anti-parasitic, anti-inflammatory, anti-HIV, and antihypertensive activities. Objective: In this review, we highlight some areas of current interest in context to azoles and their derivatives as potential chemotherapeutic agents and inhibitors. Method: A comprehensive literature search was performed for writing this review. An updated view on different derivatives of azoles and use in cancer management has been discussed. Results: Here we have discussed the present scenario of azoles and their derivatives as potential chemotherapeutic agents and inhibitors. Along with, the future perspectives of azoles in cancer prevention and treatment are also discussed. Conclusion: The information provided in this review might be useful to researchers in designing of novel and potent multifunctional azole analogues for the treatment of cancer and other multifactorial diseases.
Keywords: derivatives